Nature of X(6900) and its production mechanism at LHCb - Chang Gong (Elsevier, 2022)
We show that the Pomeron exchanges play a unique role in vector charmonium scatterings. Such a mechanism can provide a natural explanation for the nontrivial structures in the di-J/ψ spectrum observed by the LHCb Collaboration. The narrow structure X(6900), as a dynamically generated resonance pole, can arise from the Pomeron exchanges and coupled-channel effects between the J/ψ-J/ψ, J/ψ-ψ(2S) scatterings. A pole structure near the di-J/ψ threshold is also found. Meanwhile, we predict that X(6900) can produce significant threshold enhancement in the J/ψ-ψ(2S) energy spectrum which can be searched for at LHCb.